Malignant Epithelioid Mesothelioma of the Tunica Vaginalis Testis Presenting as Hydrocele in a Kidney Transplant Recipient - Brett M. Behers; Christopher W. Guske; Benjamin J. Behers; Spencer B. Kortum; Isabella G. Bermingham; Christina L. Warner; Robert I. Carey (Case Reports in Urology)
Mesotheliomas of the tunica vaginalis testis are rare malignant tumors that can present as a scrotal mass or hydrocele. These tumors are typically aggressive with high rates of recurrence and metastasis. Suspected risk factors for malignant mesothelioma include asbestos exposure, chronic inflammation, trauma, and persistent hydrocele. We report the case of a malignant epithelioid mesothelioma of the tunica vaginalis testis that presented as a finding at hydrocelectomy and was ultimately treated with radical inguinal orchiectomy. This patient was on chronic immunosuppression therapy with tacrolimus and mycophenolate mofetil secondary to a kidney transplant but had none of the common risk factors for mesothelioma formation. To our knowledge, this is the first case describing a possible connection between chronic immunosuppression and mesothelioma of the tunica vaginalis. However, future studies are needed to investigate this association and discern whether this could have played a role in our patient or if his mesothelioma formation was coincidental.